AN ASSESSMENT OF PRESENT PLANT DIVERSITY ON THE NATEWA PENINSULA, VANUA LEVU, FIJI - Andrew Powling (Reinwardtia, 2018)
POWLING, A. 2018. An assessment of present plant diversity on the Natewa Peninsula, Vanua Levu, Fiji. Reinwardtia 17(2): 125‒132. ‒‒ The Natewa Peninsula, part of the Fijian island of Vanua Levu, is naturally afforested but the forests have been extensively logged in the last 50 years. It is now planned to protect some of the forests from further logging by incorporating them into a National Park. A survey of plant species in the regenerating forests and surrounding land on the Peninsula was performed to assess the taxonomic and ecological diversity of the trees and shrubs, including figs and palms, and also the orchids presently to be found on the Peninsula. The degree of invasion by introduced plant species was also assessed. Of 67 tree and shrub species it was found that 17 were endemic to the Fijian islands, 40 others were indigenous and ten were introduced. The normal habitats of these species included dense, open and secondary forest, showing that trees with a range of ecological characteristics were still present. Endemic and indigenous species of both figs and palms were found, and also terrestrial and epiphytic orchids. No severe infestations of introduced species were observed. It is concluded that the forests of the Peninsula are of sufficient conservation value to justify National Park status.